Tác động của các cú sốc vĩ mô lên cán cân thương mại khu vực ASEAN-6: Phương pháp GVAR - Huỳnh Thái , Huy; Nguyễn Khắc Quốc , Bảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This paper utilizes a global vector autoregressive (GVAR) model for 35 countries to analyze how macroeconomic shocks from ASEAN-6’s major trading partners (such as China, US, and Japan) affect the trade balance in ASEAN-6 area. The paper's empirical results confirm the role of the US real GDP shock as an important determinant of ASEAN-6 area trade balance. The authors also find that, in the long-run, the depreciation of the CNY will lead to a significant trade surplus in China and Vietnam, while the US trade balance tends to deteriorate.
Keywords: Trade balance; International trade; GVAR; ASEAN-6